2014
DOI: 10.1007/s10508-014-0284-4
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Heteronormative Beliefs and Verbal Sexual Coercion in College Students

Abstract: Heteronormative standards for sex and romance situate men and women in a hierarchical relationship that characterizes masculinity as active and persistent and femininity as passive and responsive to male sexuality. Individuals who endorse heteronormative beliefs, such as the belief that men should dominate women sexually or that men are always ready for sex, may therefore be more approving of and experienced with behaviors that involve one partner exerting sexual pressure on the other. In the present study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 88 publications
4
63
0
Order By: Relevance
“…Studies on the relationship between gender role attitudes and intimate partner violence among Latinos have been limited (Eaton and Matamala 2014;Reed et al 2011;Santana et al 2006). Nonetheless, extant research has consistently found a link between traditional gender role attitudes and intimate partner violence perpetration, yet studies have been limited to cross-sectional examinations.…”
Section: Traditional Gender Role Attitudesmentioning
confidence: 99%
“…Studies on the relationship between gender role attitudes and intimate partner violence among Latinos have been limited (Eaton and Matamala 2014;Reed et al 2011;Santana et al 2006). Nonetheless, extant research has consistently found a link between traditional gender role attitudes and intimate partner violence perpetration, yet studies have been limited to cross-sectional examinations.…”
Section: Traditional Gender Role Attitudesmentioning
confidence: 99%
“…The assessment of the prevalence of SDS is relevant for understanding sexual health, which is related to the ability to freely enjoy and express sexuality [3]. In accordance with this , SDS has been associated with several sexual related issues, such as sexual victimization [4,5], sexual assaults [4,6,7], higher risk of acquiring sexually transmitted infections [8,9], and lower sexual satisfaction [10,11]. There are data that support the presence of SDS in Spanish society [12,13], as well as the existence of differential traditional sexual schemes for men and women, for example, in the field of sexual pleasure [14] or sexual satisfaction [15].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers suggest that women use this form of IPV because it does not require significant physical strength and may therefore be a relatively easy, yet effective, conflict tactic for them to carry out (Bjorkqvist, 1994). Others note that society has shifted such that women are increasingly becoming more violent across all forms of aggression (Eaton & Matamala, 2014;Stephens & Eaton, 2014). Given the significant increase in women's use of these aggressive tactics, there is a need for more research like this to examine what factors are influencing their increased acceptability of the perpetration of psychological aggression.…”
Section: Resultsmentioning
confidence: 99%
“…When considering Hispanic women of college age, prior research supports the assertion that parental values and behaviors have a significant influence on their daughters' intimate relationship conflict tactics (Brownridge, 2002;Eaton & Matamala, 2014;Fitzpatrick, et al, 2004). This is in part due to the importance given to familismo, a cultural framework of family importance and "connectiveness," that has been identified as a core value in Hispanic families.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation